Functional fitness and quality of life in people with intellectual and developmental disabilities: an exploratory study - Susana Diz; Miguel Jacinto; Diogo Monteiro; Rui Matos; Nuno Garrido; Aldo Costa; Raúl Antunes (Desafio Singular, 2024)
Despite physical exercise is a good indicator of health promotion, the population with intellectual and developmental disabilities tends to have high levels of physical inactivity that influence their physical fitness, health, and quality of life (QoL). The present study aimed to analyse the functional physical fitness and QoL, as well as the associations between them, of a sample of the population with IDD. Thirty-seven individuals (42,54±11,12 years) with IDD were evaluated through the tests standing up and sitting on a chair, timed up and go and walking for 6 minutes, with the purpose of analysing physical fitness and the Personal Outcome Scale (POS) to measure physical well-being. Pearson's correlations were applied and the correlation between physical well-being and the tests stand up and sit down and walk for 6 minutes was verified. The results indicate an association between functional skills measured through the tests and physical well-being, suggesting that the promotion of these skills can positively influence the physical well-being of the sample used.